Power at the Top: Mapping CEO Power and Its Influence on ESG Performance – A Bibliometric Review - Lailatun Nur Rahmah; Muhammad Saiful Hakim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
As Environmental, Social, and Governance (ESG) performance becomes a key indicator of corporate sustainability, the role of CEO power in shaping ESG outcomes warrants systematic investigation. This study aims to explore the relationship between CEO power and ESG performance by conducting a bibliometric and content analysis of relevant literature. Data were retrieved from the Scopus database using predefined keywords, resulting in 329 peer-reviewed articles published between 2018 and 2025. Bibliometric analysis was conducted using the Bibliometrix package in R, identifying publication trends, dominant themes, key contributing countries, and methodological patterns. Results indicate a growing scholarly focus on CEO influence in ESG implementation, particularly in energy-intensive sectors, with “data envelopment analysis” and “carbon emissions” emerging as central themes. Content analysis reveals that CEO power measured through tenure, duality, ownership, and political ties—exerts both enabling and constraining effects on ESG strategies. While powerful CEOs can promote long-term sustainability initiatives, excessive concentration of authority may reduce transparency and stakeholder trust. The impact of CEO power varies across ESG pillars and is influenced by contextual factors such as regulatory environments and governance structures. The study identifies research gaps in multidimensional CEO power assessment, disaggregated ESG analysis, and cross-country comparisons. These findings contribute to the theoretical understanding of executive leadership’s role in sustainability and offer directions for future empirical exploration.